Exploiting White-Collar Criminals’ Know-How: Towards a New Way of Punishment: Roberta De Paolis (The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems, 2024)
White-collar criminality is the epitome of modern-era criminality, affecting several sustainable development goals such as the promotion of access to justice and the contrast to organised crime, the provision of essential services, and the reduction of economic inequalities and vulnerabilities. For this reason, it is essential to envision a strategy that would effectively tackle white-collar crimes. This chapter argues that the enforcement of the laws for white-collar crimes should rely on a customised punishment system that combines the traditional prison sentence with community services carried out in the same context in which the white-collar crime was committed. Such a solution would guarantee at least two beneficial effects: individuals would be deterred from repeating the offence by public visibility, peers would be deterred from committing a white-collar crime, and the community would be “compensated” by a virtuous use of those skills (know-how) once improperly used by white-collar criminals.